Proposal of a holistic environmental metric based on environmental indicators - Finazzi, Guilherme Antonio; Santos, Vivianni Marques Leite (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2022)
There is no doubt Sustainability reaching is essential. Natural resources rational use is extremely important to human development. Beyond the years, this preoccupation led various institutions to elaborate legislation and international guides, as Kyoto protocol, to satisfy sustainability conditions. Agenda 2030 is the most recent instrument, whose proposals attempt to these conditions. Within this context, human activity related to Chemistry is noteworthy: to guarantee all sustainable aspects in aprocedure is a great challenge. The assessment of Sustainability in Chemistry is performed by green metrics calculations, whose utility is most appropriate in comparison of procedures than in a single procedure assessment. Due to problematics with the utilization of metrics, related to: simplifications leading to pseudo-results, need of various misunderstanding calculations and incorrect adoption of metrics, an environmental metric that attempts to current necessities related to materials and energetics consumption and to assessment of sustainability in individual chemistry procedures is proposed. The metric was elaborated aiming to attempt all environmental requirements of chemical sustainability in a simplified and reliable manner, basing on bibliographic search and expertise. The metric elaboration has a combined approach, in which reference values are established to the main indicators of sustainability, using a Soft System Methodology (SSM).